Impact of environmental noise exposure as an inducing factor on the prognosis of sudden sensorineural hearing loss: a retrospective case–control study - Wang, Yingjun; Xiong, Wenping; Sun, Xiao; Lu, Kunpeng; Duan, Fujia; Wang, Haibo; Wang, Mingming (Frontiers in Neuroscience, 2023)
Objective: To evaluate the clinical characteristics and prognostic factors associated with unilateral sudden sensorineural hearing loss (SSNHL) related to environmental noise exposure prior to its onset. Methods: Fifty unilateral SSNHL patients exposed to environmental noise prior to onset (case group) and 924 unilateral SSNHL patients without any exposure to obvious inducing factors prior to onset (control group) were enrolled between January 2018 and October 2022. We retrospectively analyzed differences between both groups using Chi-square and Fisher’s exact tests, independent t-tests, Mann–Whitney U tests as appropriate before and after propensity score matching (PSM) based on sex, age, and initial pure tone average (PTA). Prognostic factors for the case group were analyzed using univariate and multivariate logistic analyses between the effective and ineffective groups. Results: Before PSM, significant differences were noted in age, sex, time to treatment, proportion of combined diabetes mellitus, initial PTA, hearing gain, incidence of vertigo or aural fulness, the rate of vestibular dysfunction or inner ear MRI abnormalities, the effective rate, the glucose and homocysteine levels, and the proportion of audiogram curve types (P < 0.05) between both groups. After PSM, compared to the control group, a longer time to treatment (Z= -3.02, P < 0.05), higher final PTA (Z= -2.39, P < 0.05), lower hearing gain (Z= -3.46, P < 0.05), lower rate of vestibular dysfunction (X2= 55.1, P < 0.001), and lower effective rate (X2= 4.87, P < 0.05) were observed in the case group. There was a significant difference between the audiogram curve types in both groups (X2= 14.9, P < 0.05). Time to treatment (95% confidence interval: 0.692–0.965, P < 0.05) and final PTA (95% confidence interval: 0.921–0.998, P < 0.05) were associated with the clinical outcomes for the case group. Conclusion: Unilateral SSNHL patients exposed to environmental noise triggers prior to onset showed a poorer effective rate and lower rate of vestibular dysfunction than those who were not. The time to treatment and final PTA were associated with the prognosis of these patients.